2020
DOI: 10.1186/s12903-020-01243-y
|View full text |Cite
|
Sign up to set email alerts
|

“It’s really no more difficult than putting on fluoride varnish”: a qualitative exploration of dental professionals’ views of silver diamine fluoride for the management of carious lesions in children

Abstract: Background Despite evidence that Silver Diamine Fluoride (SDF) can be effective in managing carious lesions in primary teeth, the use of SDF in the UK remains limited. This study explored dental professionals’ views and experiences of using SDF for managing carious lesions in children. In addition, it explored what they perceived to be the advantages, disadvantages, barriers and enablers to the use of SDF in practice. Methods Fifteen semi-structured face-to-face or over-the-phone interviews were conducted wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 28 publications
3
25
0
Order By: Relevance
“…It can also be used to manage extensive and non-restorable carious lesions without pain/infection until tooth exfoliation occurs [6]. There has been an increasing interest to adopt this new method in dental practices in developed countries such as the UK [26] particularly given its relatively easy application [27].…”
Section: Discussionmentioning
confidence: 99%
“…It can also be used to manage extensive and non-restorable carious lesions without pain/infection until tooth exfoliation occurs [6]. There has been an increasing interest to adopt this new method in dental practices in developed countries such as the UK [26] particularly given its relatively easy application [27].…”
Section: Discussionmentioning
confidence: 99%
“…An interview schedule was developed to examine acceptability of SDF from a parent and child perspective, using age-appropriate language (Additional file 1). This interview schedule was informed by the literature as well as previous work conducted by the authors, exploring Dental Care Professionals' acceptability of SDF [7]. Using clinical photographs of patients before and after SDF treatment (Additional file 2), questions were focused on the acceptability of SDF, together with factors that influence decision-making regarding other treatment options.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, one side effect is that the carious lesion is stained black. It has been suggested that this staining could be a barrier to its use for some parents, especially for anterior teeth [7]. Yet, there is other evidence to suggest that parents may view this discoloration as a positive sign that the treatment has been effective [2].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, other research has found that overall, the black stains were well accepted by both parents and patients, whereas this acceptance was low among dental professionals [ 7 ]. Therefore, dental professionals may not offer SDF as a treatment option if they assume that parents are unlikely to accept it because of concerns about the aesthetics [ 9 ].…”
Section: Introductionmentioning
confidence: 99%